2020
DOI: 10.3390/insects11020133
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Toxicity Interactions between Plant Essential Oil Components against the Common Bed Bug (Cimex lectularius L.)

Abstract: Management of the common bed bug (Cimex lectularius L.) necessitates the use of multiple control techniques. In addition to synthetic pesticides and mechanical interventions, plant-derived essential oils represent one of the control options. Mixtures of two or more essential oil components (monoterpenoids) exhibit synergistic toxicity effects against insects due to increased cuticular penetration. Monoterpenoids, such as carvacrol, eugenol and thymol, are neurologically active and inhibit the nerve firing acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Studies on the structure-function relationship of EO constituents point out that molecular shape, degree of saturation, volatility and type of functional groups contribute to the efficacy of natural insecticides [ 102 ]. Besides, it has been well documented that EO compounds act in synergy and affect multiple targets in pest insects [ 93 , 94 , 103 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the structure-function relationship of EO constituents point out that molecular shape, degree of saturation, volatility and type of functional groups contribute to the efficacy of natural insecticides [ 102 ]. Besides, it has been well documented that EO compounds act in synergy and affect multiple targets in pest insects [ 93 , 94 , 103 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main chemical classes of volatile organic compounds present in plant essential oils are terpenes, phenol-derived aromatic components and aliphatic components, and their bioactivity is frequently a result of synergy among constituents [ 12 ]. Recently, synergistic effects of essential oil compounds or mixtures of essential oils have been demonstrated for various types of bioactivity, including antioxidant, antimicrobial, and insecticide effects [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The only exception to this may be prior use of EcoRaider, which did impact both viability and efficacy of Aprehend even when the residues were three weeks old. This is unfortunate, since recent research into essential oils for bed bug control has demonstrated their potential utility as alternatives to conventional chemicals for bed bug control and resistance management [ 6 , 8 ]. Unlike their observed synergistic effect with chemical insecticides [ 30 ], essential oils appear to have a detrimental impact on B. bassiana spores.…”
Section: Discussionmentioning
confidence: 99%
“…Biopesticide products are of growing interest [ 4 ]. Botanical and non-chemical control methods such as the use of natural compound mixtures [ 6 , 7 , 8 ], microbial control using Serratia marcescens , Pseudomonas fluorescens , and Bacillus thuringiensis israelensis [ 9 ] and the use of entomopathogenic fungi like Metarhizium anisopliae [ 10 , 11 ] and Beauveria bassiana [ 12 , 13 , 14 , 15 ] are being investigated.…”
Section: Introductionmentioning
confidence: 99%